Use and Usability Of Custom-Made Knee-Ankle-Foot Orthoses In Polio Survivors with Knee Instability: A Cross-Sectional Survey - Bart Raijmakers; Roelofine A. Berendsen-de Gooijer; Hilde E. Ploeger; Fieke S. Koopman; Frans Nollet; Merel-Anne Brehm (Medical Journals Sweden, 2022)
Objective: To investigate the use of custom-made knee-ankle-foot orthoses in daily life and differences in usability factors of knee-ankle-foot orthoses between users and discontinued users. Design: Cross-sectional survey study. Subjects: A total of 163 polio survivors provided with a knee-ankle-foot orthosis at an outpatient clinic of a university hospital. Methods: Use and usability of knee-ankle-foot orthoses in daily life were assessed with a postal questionnaire. Usability factors were formulated using the International Organization for Standardization (ISO) 9241-11 standard. Results: A total of 106 respondents (65%) returned the questionnaire. Of these, 98 were eligible for analysis. Seventy-four respondents (76%) reported using their knee-ankle-foot orthosis. Compared with discontinued users (24%), users experienced more limitations when walking without an orthosis (p = 0.001), were more often experienced with wearing a previous orthosis (p < 0.001) and were more often prescribed with a locked rather than a stance-control knee-ankle-foot orthosis (p = 0.015). Furthermore, users reported better effectiveness of their knee-ankle-foot orthosis (p < 0.001), more satisfaction with goals of use and knee-ankle-foot orthosis-related aspects (p < 0.001). Conclusion: The majority of polio survivors used their custom-made knee-ankle-foot orthoses in daily life. Factors related to continued use, such as walking ability without orthosis, expectations of the orthosis, previous orthosis experience and type of knee-ankle-foot orthosis provided, should be considered and discussed when prescribing a knee-ankle-foot orthosis in polio survivors. LAY ABSTRACT Knee-ankle-foot orthoses for knee instability are commonly prescribed in polio survivors to enhance safe ambulation. This survey investigated the use of knee-ankle-foot orthoses in daily life and differences in factors of usability between users and discontinued users. Seventy-six percent of polio survivors used their custom-made knee-ankle-foot orthosis in daily life. Important usability factors that were related to continued use of knee-ankle-foot orthoses were low perceived walking ability status without orthosis, previous orthosis experience, high perceived effectiveness and satisfaction when standing and walking with a knee-ankle-foot orthoses. When prescribing a custom-made knee-ankle-foot orthoses it is important to consider these factors and discuss goals of use and expected benefits of the knee-ankle-foot orthoses with the patient, especially in relation to perceived walking limitations and activities in daily life.